Glucocorticoid Programing of the Mesopontine Cholinergic System - Borges, Sónia; Coimbra, Bárbara; Soares-Cunha, Carina; Ventura-Silva, Ana Paula; Pinto, Luisa; Carvalho, Miguel M.; Pêgo, José M.; Rodrigues, Ana J.; Sousa, Nuno (Frontiers in Endocrinology, 2013)
Stress perception, response, adaptation and coping strategies are individually distinct, and the sequel of stress and/or glucocorticoids is also distinct between subjects. In the last years, it has become clear that early life stress is a powerful modulator of neuroendocrine stress-responsive circuits, programming intrinsic susceptibility to stress, and potentiating the appearance of stress-related disorders such as depression, anxiety and addiction. Herein we were interested in understanding how early life experiences reset the normal processing of negative stimuli, leading to emotional dysfunction. Animals prenatally exposed to glucocorticoids (iuGC) present hyperanxiety, increased fear behaviour and hyper-reactivity to negative stimuli. In parallel, we found a remarkable increase in the number of aversive 22kHz ultrasonic vocalizations in response to an aversive cue. Considering the suggested role of the mesopontine tegmentum cholinergic pathway, arising from the laterodorsal tegmental nucleus (LDT) and pedunculopontine tegmental nucleus (PPT), in the initiation of 22kHz vocalizations and hypothetically in the control of emotional arousal and tone, we decided to evaluate the condition of this circuit in iuGC animals. Notably, in a basal situation, iuGC animals present increased choline acetyltransferase (ChAT) expression in the LDT and PPT, but not in other cholinergic nuclei, namely in the nucleus basalis of Meynert. In addition, and in accordance with the amplified response to an adverse stimulus of iuGC animals, we found marked changes in the cholinergic activation pattern of LDT and PPT regions. Altogether, our results suggest a specific cholinergic pathway programing by prenatal GC, and hint that this may be of relevance in setting individuals stress vulnerability threshold.